2011
DOI: 10.1001/archsurg.2011.102
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Incidentally Discovered, Nonfunctioning Pancreatic Endocrine Tumors

Abstract: Objectives To describe the characteristics and outcomes after resection of incidentally discovered, nonfunctioning pancreatic endocrine tumors (PETs). Design Case series. Setting Academic hospital. Patients Consecutive patients with an incidentally identified, nonfunctioning PET resected from May 1, 1977, through July 31, 2009. Main Outcome Measures Operative morbidity and survival after resection. Results A total of 139 patients with median age of 56 years (range, 21–85 years) underwent resection; t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
144
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(160 citation statements)
references
References 15 publications
12
144
0
1
Order By: Relevance
“…In our study, there was a significant association between pT, tumour grade 2004 (p = 0.005) and vascular invasion (p = 0.005), explaining the association between pT and prognosis through common mechanisms of anaplasia and invasive tumour properties. pN1 was found in 20.0% of PNEN, in accordance with other observations [41,[45][46][47]50] and was strongly predicted by older age. Age exceeding 60 years has been shown to be associated with lower survival, even in patients with low-grade (G1) gastroenteropancreatic PNENs [51].…”
Section: Ptnmsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, there was a significant association between pT, tumour grade 2004 (p = 0.005) and vascular invasion (p = 0.005), explaining the association between pT and prognosis through common mechanisms of anaplasia and invasive tumour properties. pN1 was found in 20.0% of PNEN, in accordance with other observations [41,[45][46][47]50] and was strongly predicted by older age. Age exceeding 60 years has been shown to be associated with lower survival, even in patients with low-grade (G1) gastroenteropancreatic PNENs [51].…”
Section: Ptnmsupporting
confidence: 91%
“…Within the study, PNEN size ranged from 1.2-12.5 cm, in accordance with the published results [41,[45][46][47]. Prognostic value has been attributed to the size of PNEN.…”
Section: Tumour Sizesupporting
confidence: 89%
See 1 more Smart Citation
“…PNETs are highly heterogeneous neoplasms presenting a spectrum of biologic behavior (7,8). Aggressive progression can even be observed in incidentally detected and small tumors (9). Potential prognostic factors, including mitoses, vascular invasion, metastasis, necrosis, Ki-67 expression, and nuclear grade, are mostly based on pathological examination (2,3,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors suggest that surgery is indicated in any case because NF-PNETs should always be considered as potentially malignant tumors, and a proper histological examination of the tumor (including the mitotic and Ki-67 indexes) is possible only on the resected specimen. 21,22 Previous studies have reported that several factors are associated with survival, including age, 23,24 tumor size, 9,23,[25][26][27] grade/differentiation, 14,24,25,28 LN status, 25,29 presence of distant metastases, 14,23,24,29 and surgical resection. 14,23 Age has consistently been found to be a powerful predictor of survival in patients undergoing resection of PNETs.…”
Section: Discussionmentioning
confidence: 99%